Implementation of the Fuzzy Game Theory Logic Method in Competition for Local Skincare Brand Products (Ms. Glow with Scarlett Whitening) - Rosa Fitrie; Arnah Ritonga (PT FORMOSA CENDEKIA GLOBAL, 2022)
The competition for skincare products is getting tighter so that the owners of skincare companies are expected to be able to predict what marketing strategies their competitors will have and be able to analyze what attributes suit consumer needs. To get the right marketing strategy, namely by applying the fuzzy game theory logic method. The purpose of this research is to find out what attributes are preferred by consumers in order to obtain optimal marketing strategies from two local skincare product companies that are studied using fuzzy game theory by relying on the attributes that are prioritized by consumers. The optimal marketing strategy is a strategy on product quality with a game value of -0.243. Scarlett Whitening uses product quality attributes as a marketing strategy to maximize profits. Meanwhile, to minimize the losses, Ms. skincare products. Glow uses product quality attributes as well.